Effects of double ligation of Stensen's duct on the rabbit parotid gland. (April 2014) - Maria, OM; Maria, SM; Redman, RS; Maria, AM; Saad El-Din, TA; Soussa, EF; Tran, SD
Abstract Salivary gland duct ligation is an alternative to gland excision for treating sialorrhea or reducing salivary gland size prior to tumor excision. Duct ligation also is used as an approach to study salivary gland aging, regeneration, radiotherapy, sialolithiasis and sialadenitis. Reports conflict about the contribution of each salivary cell population to gland size reduction after ductal ligation. Certain cell populations, especially acini, reportedly undergo atrophy, apoptosis and proliferation during reduction of gland size. Acini also have been reported to de-differentiate into ducts. These contradictory results have been attributed to different animal or salivary gland models, or to methods of ligation. We report here a bilateral double ligature technique for rabbit parotid glands with histologic observations at 1, 7, 14, 30, 60 days after ligation. A large battery of special stains and immunohistochemical procedures was employed to define the cell populations. Four stages with overlapping features were observed that led to progressive shutdown of gland activities: 1) marked atrophy of the acinar cells occurred by 14 days, 2) response to and removal of the secretory material trapped in the acinar and ductal lumens mainly between 30 and 60 days, 3) reduction in the number of parenchymal (mostly acinar) cells by apoptosis that occurred mainly between 14–30 days, and 4) maintenance of steady-state at 60 days with a low rate of fluid, protein, and glycoprotein secretion, which greatly decreased the number of leukocytes engaged in the removal of the luminal contents. The main post- ligation characteristics were dilation of ductal and acinar lumens, massive transient infiltration of mostly heterophils (rabbit polymorphonuclear leukocytes), acinar atrophy, and apoptosis of both acinar and ductal cells. Proliferation was uncommon except in the larger ducts. By 30 days, the distribution of myoepithelial cells had spread from exclusively investing the intercalated ducts pre-ligation to surrounding a majority of the residual duct-like structures, many of which clearly were atrophic acini. Thus, both atrophy and apoptosis made major contributions to the post-ligation reduction in gland size. Structures also occurred with both ductal and acinar markers that suggested acini differentiating into ducts. Overall, the reaction to duct ligation proceeded at a considerably slower pace in the rabbit parotid glands than has been reported for the salivary glands of the rat.